Breastfeeding Counseling to Improve Self Efficacy of Post Partum Mothers in Providing Exclusive Breastfeeding - Sherly Jeniawaty; Rijanto Rijanto (Humanistic Network for Science and Technology (HNST), 2018)
Coverage of breastfeeding in Indonesia is still reached 61.5% of the national target (80%). This study used a quasi-experimental design with pre and post test approach control group. Data was collected using Breastfeeding Self-Efficacy Scale- Short Form (BSES-SF). The results of further analysis concluded that there were differences between the mean difference in scale between the groups (p = 0.000). Breastfeeding counseling intervention group self-efficacy can improve self efficacy postpartum mothers in exclussive breastfeeding. Psychological and emotional condition stable will increase interest and motivation to learn the mother.Keywords: Counseling, Exclusive breastfeeding